ANALISIS TINDAK TUTUR JENDERAL GATOT NURMANTYO DARI PERSKPEKTIF FILSAFAT RELATIVITAS BAHASA - Dewi, Yuli Rahmawati; Syihabuddin, Syihabuddin (Universitas Sebelas Maret, 2021)
Missunderstandings can happen between language users. Based on Language Relativity theory, it’s because language depends on the knowledge, background and agreement of its user. This research studies a language missunderstanding caused by the utterances stated by Indonesia National Armed Force 2015-2017 Commander, in CNN Indonesia interview. The interview’s telling about him commanding his array to re-watch G30S/PKI movie. The research purposes to explain the types and the influence of the utterances stated, the caused and the form of the missunderstanding, and the language relativity happens in Linguistics point of views using descriptive qualitative method and gather and writing technique. The data taken from CNN Indonesia official youtube on September 18, 2017 tittled Panglima TNI Perintahkan Seluruh Jajarannya untuk Nobar Film G30S/PKI. Based on Austin (1962) Speech Act theory, there are two types speech act found. There are Locutionary Act and Ilocutionary Act. The Ilocutionary Act utterances are included to Expositives, Verdictive and Commisives types. It gives impact as if the hearer must watch the G30S/PKI movie. The Context of the utterance was meant for the Armed Force he lead at the time that might be accepted differently by those who come from different backgrounds.This shows the language relativity phenomenon